2010
DOI: 10.1007/s11606-010-1392-z
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Institutional Quality Improvement Initiative to Transform Education for Chronic Illness Care in Resident Continuity Practices

Abstract: BACKGROUND: There is a gap between the need for patient-centered, evidence-based primary care for the large burden of chronic illness in the US, and the training of resident physicians to provide that care. OBJECTIVE: To improve training for residents who provide chronic illness care in teaching practice settings. DESIGN: US teaching hospitals were invited to participate in one of two 18-month Breakthrough Series Collaboratives-either a national Collaborative, or a subsequent California Collaborative-to implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 24 publications
0
55
0
1
Order By: Relevance
“…The evidence from these diabetes self-management implementation studies supports the provision of self-management for people with diabetes as they show consistent improvement in process outcomes, 237 Many of these studies, however, are uncontrolled before-and-after studies with the inherent methodological limitations. The only cluster randomised trial, in the very specific context of including CHWs in multidisciplinary collaborative programmes for diabetes improvement, showed improved process outcomes (documented self-management goals) but no difference in clinical outcomes.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The evidence from these diabetes self-management implementation studies supports the provision of self-management for people with diabetes as they show consistent improvement in process outcomes, 237 Many of these studies, however, are uncontrolled before-and-after studies with the inherent methodological limitations. The only cluster randomised trial, in the very specific context of including CHWs in multidisciplinary collaborative programmes for diabetes improvement, showed improved process outcomes (documented self-management goals) but no difference in clinical outcomes.…”
Section: Discussionmentioning
confidence: 80%
“…Five papers reporting three studies focused on T1DM, [251][252][253][254][255] eight focused on T2DM, [246][247][248][249][250]260,261,264 the remaining 15 included mixed populations. [237][238][239][240][241][242][243][244][245][256][257][258][259]262,263 Thirteen of the studies were conducted in the USA, [237][238][239][244][245][246][247][248][256][257][258][259]262 one in the UK, 240 three from Germany (in five papers), 251,[253][254][255]260 three from Austria, 250,…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The national Academic/California Chronic Care Collaboratives showed that systematic practice and education redesign is achievable across disparate resident continuity clinics. 13 To their delight, researchers found teams that achieved better outcomes on clinical indicators reported more professional work satisfaction. 14 These papers point out an important first step in developing a transformed practicethe leaders of the practice must seek training in improvement techniques and be able to bring these concepts home to their institutions.…”
Section: Sound Familiar?mentioning
confidence: 99%
“…[15][16][17][18][19][20] Early residency education redesign initiatives, including the Academic Chronic Care Collaborative, 21,22 Health Resources and Services Administration (HRSA) efforts, 23 and Veterans Affairs Centers of Excellence in Primary Care Education, are significant investments. 24 However, most residents still train in poorly organized practices, with few, if any, PCMH elements.…”
Section: Introductionmentioning
confidence: 99%